P116 Chemical characterisation of the indoor air quality of a university hospital: contribution of outdoor and indoor sources of air pollutants. (1st September 2016) - Scheepers, Paul TJ; Wel, Luuk van; Beckmann, Gwendolyn; Anzion, Rob
Abstract : Local outdoor sources of air pollution may become a threat to indoor air quality (IAQ). The aim of this study was to find out if local outdoor sources of air pollution have an impact on IAQ of a hospital. We characterised emissions from a helicopter and from diesel-powered emergency power supply units as suspected causes of odour complaints in five university hospital buildings. IAQ was characterised at eleven locations and at two other university buildings for reference. In addition, outdoor air was collected simultaneously at the helicopter platform and at the two reference locations. The following measurements were performed simultaneously over a period of two weeks: volatile organic compounds (VOC), acrolein, formaldehyde, nitrogen dioxide (NO2), respirable particulate matter (PM-4.0 and PM-2.5) and their benz[a]pyrene (B[a]P) contents. Concentrations of NO2 (4.9–17.4 µg/m 3 ) and formaldehyde (2.5–6.4 µg/m 3 ) were similar on all indoor and outdoor locations, reflecting general outdoor air quality. Week average VOC concentrations with a median of 119 µg/m3 (range: 331–2, 450 µg/m 3 ) were clearly elevated and the higher values were related to disinfection (alcohols) and laboratory practices (aromatic hydrocarbons). Median values were fivefold higher in laboratories (316 µg/m 3 ) compared to offices (57.0 µg/m 3 ). With values of < 1.0 µg/m 3 concentrations of PM-4.0 were lower in buildings serviced with air filtered by a > 99.95% efficiency particle filter, compared to buildings using a standard 80–90% efficiency PM-filter (p < 0.01). In buildings with high efficiency PM-filters, median B[a]P concentrations were <0.3 pg/m 3 compared to levels of 51.8 ± 13.2 pg/m 3 in buildings with standard PM-filters. No indications were found that confirm a contribution of known local sources such as fuels or combustion engines to any of the IAQ parameters measured in this study. Chemical IAQ was primarily driven by known indoor sources and activities.